PEMETAAN KASUS COVID-19 MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI PROVINSI BALI 2020 - Wangsa Ariadi, I Gede Bagus; Mahayasa Adiputra, I Nyoman; Saptiono Mulana, Viktorinus Alfred (Jurnal Teknologi Informasi dan Komputer, 2022)
ABSTRACT Background Covid-19 is a new virus that first appeared at the end of 2019, the covid-19 virus is zoonotic, this virus can cause symptoms from mild to severe. The Covid-19 virus can spread quickly if you have direct contact with a positive person. The purpose of this study was to find out how the description of the distribution of COVID-19 cases in Bali Province in 2020 using GIS. Subjects and Methods: This research is descriptive using in-depth library study method. The population in this study was all COVID-19 data in Indonesia in 2020. The sampling technique in this study used the purposive sampling method with a sample of all Covid-19 data in the Province of Bali 2020. Results: From the results of the mapping conducted using QGIS, it was found that the area with The highest number of COVID-19 is Badung, Denpasar, and Gianyar. The peak of cases was in December with the highest accumulation of cases in Denpasar (4759), Badung (3139), and Gianyar (238). Conclusion: This study can be concluded that by mapping COVID-19 cases in the province of Bali using GIS, it can be seen about the distribution of Covid-19 cases in each area in the Province of Bali. Keywords: GIS, Covid-19, Mapping ABSTRAK Latar Belakang: Covid-19 merupakan virus baru yang pertama kali muncul pada akhir 2019, virus covid-19 menular secaraa zoonosis virus ini dapat menyebabkan gejala dari ringan samapi berat. Virus covid-19 dapat menyebar dengan cepat jika melakukan kontak langsung dengan orang posiftif. Tujuan dari penelitian ini untuk mengetahui bagaimana gambaran sebaran kasus covid-19 di Provinsi bali tahun 2020 menggunakan SIG. Subjek dan Metode: Penelitian ini adalah deskriptif menggunakan metode studi Pustaka mendalam. Populasi pada penelitian ini adalah seluruh data covid-19 di Indonesia tahun 2020. Hasil: Dari hasil pemetaan yang dilakukan menggunakan QGIS diperoleh daerah yang memiliki jumlah kasus covid- 19 tertinggi iyalah Badung, Denpasar, dan Gianyar. Puncak kasus berada pada bulan desember dengan akumulasi kasus tertinggi berada di kabupaten Denpasar (4759), Badung (3139), dan Gianyar (238).Kesimpulan: Penelitian ini dapat disimpulkan bahwa dengan pemetaan kasus covid-19 di provinsi bali menggunakan SIG dapat diketahui tentang sebaran kasus covid-19 pada setiap daerah di Provinsi Bali Kata kunci: SIG, Covid-19, Pemetaan